Clinical Advancements in the Targeted Therapies against Liver Fibrosis. (24th November 2016) - Bansal, Ruchi; Nagórniewicz, Beata; Prakash, Jai
Abstract : Hepatic fibrosis, characterized by excessive accumulation of extracellular matrix (ECM) proteins leading to liver dysfunction, is a growing cause of mortality worldwide. Hepatocellular damage owing to liver injury leads to the release of profibrotic factors from infiltrating inflammatory cells that results in the activation of hepatic stellate cells (HSCs). Upon activation, HSCs undergo characteristic morphological and functional changes and are transformed into proliferative and contractile ECM-producing myofibroblasts. Over recent years, a number of therapeutic strategies have been developed to inhibit hepatocyte apoptosis, inflammatory responses, and HSCs proliferation and activation. Preclinical studies have yielded numerous targets for the development of antifibrotic therapies, some of which have entered clinical trials and showed improved therapeutic efficacy and desirable safety profiles. Furthermore, advancements have been made in the development of noninvasive markers and techniques for the accurate disease assessment and therapy responses. Here, we focus on the clinical developments attained in the field of targeted antifibrotics for the treatment of liver fibrosis, for example, small molecule drugs, antibodies, and targeted drug conjugate. We further briefly highlight different noninvasive diagnostic technologies and will provide an overview about different therapeutic targets, clinical trials, endpoints, and translational efforts that have been made to halt or reverse the progression of liver fibrosis.